2006
DOI: 10.1021/ja062851y
|View full text |Cite
|
Sign up to set email alerts
|

A Third Mode of DNA Binding:  Phosphate Clamps by a Polynuclear Platinum Complex

Abstract: We describe a 1.2 A X-ray structure of a double-stranded B-DNA dodecamer (the Dickerson Dodecamer, DDD, [d(CGCGAATTCGCG)]2) associated with a cytotoxic platinum(II) complex, [{trans-Pt(NH3)2(NH2(CH2)6(NH3+)}2-mu-{trans-Pt(NH3)2(NH2(CH2)6NH2)2}] (TriplatinNC). TriplatinNC is a multifunctional DNA ligand, with three cationic Pt(II) centers, and directional hydrogen bonding functionalities, linked by flexible hydrophobic segments, but without the potential for covalent interaction. TriplatinNC does not intercalat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
1
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(148 citation statements)
references
References 58 publications
(87 reference statements)
5
134
1
8
Order By: Relevance
“…Farrell et al have described a discrete binding mode based on interactions that utilize exclusively backbone functional groups [30 ]. The new binding mode was observed in the crystal structure of a double-stranded B-DNA dodecamer with TriplatinNC (13) (Figure 2b).…”
Section: Non-covalent Interactions With Dnamentioning
confidence: 97%
“…Farrell et al have described a discrete binding mode based on interactions that utilize exclusively backbone functional groups [30 ]. The new binding mode was observed in the crystal structure of a double-stranded B-DNA dodecamer with TriplatinNC (13) (Figure 2b).…”
Section: Non-covalent Interactions With Dnamentioning
confidence: 97%
“…175, 176 More recently it has been shown to be able to form phosphate clamps with the backbone of DNA 177 and have possible interactions with membrane phospholipids.…”
Section: Bbr3464mentioning
confidence: 99%
“…For multinuclear platinum complexes it has been shown that hydrogen bonding and electrostatic binding between the bridging ligand and the DNA helix is important in stabilising and directing the type of DNA adducts formed. 19,[26][27][28] The ligands synthesised in this work are therefore capable of acting as both hydrogen bond acceptors/donors and when pre-associated in the DNA minor groove, can potentially form hydrogen bonds to the bases as well as ion-dipole interactions with the anionic DNA backbone.…”
Section: Ligand Synthesismentioning
confidence: 99%